The correlation between the expression of genes involved in drug metabolism and the blood level of tacrolimus in liver transplant receipts - Jianhai Wang (Nature Portfolio, 2017)
Abstract Immunosuppressive medications, such as tacrolimus and mycophenolate mofetil, are commonly used for reducing the risk of organ rejection in receipts of allogeneic organ transplant. The optimal dosages of these drugs are required for preventing rejection and avoiding toxicity to receipts. This study aimed to identify the correlation between the expression profiling of genes involved in drug metabolism and the blood level of tacrolimus in liver transplant receipts. Sixty-four liver transplant receipts were enrolled in this retrospective study. Receipts were divided into low (2–5.9 ng/ml) and high (6–15 ng/ml) tacrolimus groups. Clinical assessment showed that the blood level of tacrolimus was inversely correlated with the liver function evaluated by blood levels of total bilirubin and creatinine. Compared to the high tacrolimus group, expression levels of six cytochrome P450 enzymes, CYP1A1, CYP2B6, CYP3A5, CYP4A11, CYP19A1, and CYP17A1 were significantly higher in the low tacrolimus group. The expression levels of these genes were negatively correlated with the tacrolimus blood level. Enzyme assays showed that CYP3A5 and CYP17A1 exerted direct metabolic effects on tacrolimus and mycophenolate mofetil, respectively. These results support clinical application of this expression profiling of genes in drug metabolism for selection of immunosuppressive medications and optimal dosages for organ transplant receipts.